Management Strategy of Actual Tabloid Banjarmasin, South Kalimantan In Digital Era - Sujoko, Anang; Ludigdo, Unti; Muhammad, Iqbal (Technium Social Sciences Journal, 2021)
The diffusion of the Internet has affected the print media industry, how the industry has responded to this new platform, and the impact of this response. The results documenting the magnitude of the negative impact of Internet penetration on print media circulation in this case is the Tabloid. This study aims to find out how Interpretative Social Science (ISS) is used to uncover actual Tabloid management strategies in the digital age, so that complete data will be obtained and researchers can explain comprehensively. The subjects of this study were the general leaders, editors and reporters of the Tabloid Aktual, as well as the employees of PT Abid Media Mandiri South Kalimantan, who published this media using interpretative qualitative methods. In this case, the newspaper responded to the diffusion of the Internet by creating an online version as well as a strategic response that quickly proved dangerous because online media circulation cannibalized print circulation. Print newspapers and Tabloids are at a disadvantage situation because they have degradation inflow and incoming funds due to the presence of online media in the digital age. As you know, it causes a decrease in proportional subscription from readers and offline advertising revenue. This should required corporate strategy and dynamic capabilities and appropriate media convergence to maximize strategic management that seeks to understand the basis of competitive advantage and company performance in a variety of ways. Looking at the Aktual Tabloid from January to July 2019, researchers found content that showed the results of collaboration with a number of local governments, including mayor, district and provincial governments so that could say Tabloid Aktual could survive in the digital era by collaborating with internal and external parties. The ideology of the local mass media is in line with postmodern which in the language game is more ironic, the purpose of this postmodern culture is no longer the effectiveness of the message. Postmodern is no longer looking for the depth of the meaning of communication, but only looking for fun by "playing with language" and the meaning in writing will be increasingly biased in accordance with the interests and ownership of the media with public figures and Taboid Actual media management strategy is closely related to the Industrial Organization (IO) Model.